Prevalence of Iron Deficiency with and Without Anemia Among Immigrant’ People in Al-Azrakeen Area, Sana’a City, Yemen - Dekra El-Aghbary; Rashad A Thabet; Ebtesam M Al-Zabedi, PhD; Aref N Al-Afif, MSc. (Annals of Medicine and Medical Sciences)
Background: The prevalence of iron deficiency with or without anemia is still remains the common clinical problem worldwide. Iron deficiency with and without anemia may be more prevalent among migrants due to disadvantaged life conditions. The aim of this study was to estimate the prevalence of iron deficiency with and without anemia among immigrants in Al-Azrakeen area, Sana’a City. Subjects and Methods: Out of 2300 immigrant population in Al-Azrakeen area, 223 participants were randomly chosen, aged from 5 to 50 years (134 children and 89 adults). The study included measurement of hematological parameters and serum iron indices. All data were analyzed using SPSS version 26. Results: The prevalence of iron deficiency among the total immigrant population, adult and children was 21.5%, 19.1% and 23.1%, respectively. While the prevalence of IDA among total immigrants, adults and children was 6.7%, 4.5% and 8.2%, respectively. Statistically signifcant association was observed between iron deficiency anemia and age of immigrant adults (p=0.05). Conclusion: This study concludes that iron deficiency and iron deficiency anemia are prevalent among immigrants in Al-Azrakeen area, Sana’a City, Yemen. Children are at higher prevalence of developing iron deficiency with or without anemia.